Determinants of Good Corporate Governance (Empirical Studies on Companies Listed on The IDX) - Praditha, Riza; Megawati, Megawati; Agustuty, Lasty (SENTRALISASI, 2022)
The purpose of this study is the role of ownership concentration, firm size, and leverage in influencing good corporate governance. This research design is quantitative. The population used is 45 companies indexed LQ45 on the Indonesia Stock Exchange and with the Purposive Sampling method, obtained 17 companies with 3 years of observation, so the number of samples in this study is 51. The results show that the concentration of ownership, company size, and leverage have a significant effect. The test results show a positive and significant effect on the implementation of corporate governance partially for each variable and simultaneously for all variables.